2020
DOI: 10.1161/circ.142.suppl_3.13919
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 13919: Race and Gender Specific High Sensitivity Troponin-t Cutoff Values Improve Detection in Patients’ With Ischemic Heart Disease

Abstract: Introduction: Death rates from acute coronary syndrome events (ASCE) are 30% higher in African Americans than in Caucasians. A potential reason for this disparity is the underdiagnosis of ACSE due to race-specific differences in blood levels of cardiac troponin-T (cTnT), the biomarker of choice for the exclusion of myocardial injury. Hypothesis: Race- and gender-specific high-sensitivity cTnT (hs-cTnT) cutoff values will improve the detection of myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, it is unclear whether diagnostic performance was consistent across key patient subgroups, such as men, women, white patients, and non‐white patients and there is a paucity of prior data evaluating sex or race differences in algorithm performance. Prior studies have demonstrated significant differences in 99th percentile hs‐cTnT values among men versus women and white patients versus non‐white patients 15–18 . In addition, it has been hypothesized that greater racial diversity of US ED patients may explain differences in the diagnostic performance of the ESC 0/1‐h algorithm in the United States versus Europe and Australasia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is unclear whether diagnostic performance was consistent across key patient subgroups, such as men, women, white patients, and non‐white patients and there is a paucity of prior data evaluating sex or race differences in algorithm performance. Prior studies have demonstrated significant differences in 99th percentile hs‐cTnT values among men versus women and white patients versus non‐white patients 15–18 . In addition, it has been hypothesized that greater racial diversity of US ED patients may explain differences in the diagnostic performance of the ESC 0/1‐h algorithm in the United States versus Europe and Australasia.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated significant differences in 99th percentile hs‐cTnT values among men versus women and white patients versus non‐white patients. 15 , 16 , 17 , 18 In addition, it has been hypothesized that greater racial diversity of US ED patients may explain differences in the diagnostic performance of the ESC 0/1‐h algorithm in the United States versus Europe and Australasia. Thus, it is plausible that the performance of the ESC 0/1‐h algorithm may differ based on demographics.…”
Section: Introductionmentioning
confidence: 99%